(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: This paper aimed to assess the change of the early initiation of breastfeeding (within one hour of birth) amongst postpartum women in a hospital-based intervention during 2022-2023. Methods: The study used a quasi-experimental design that used data before and after an intervention to evaluate the effectiveness of the intervention. The total number of postpartum women was 400 with 2 data collection periods: Jan-Apr, 2022 and Sep-Dec, 2023. Results: The results showed that early initiation of breastfeeding amongst postpartum women increased from 47.5% to 97.7%, with an 50.2% increase in percentage (p<0.05). Conclusions: The results show that intervention to promote early breastfeeding for postpartum mothers at Bokeo Provincial General Hospital is effective. We recommend that health workers’ intervention and support for mothers according to step 2 of the Baby-Friendly Hospital Initiative (BFHI) is an effective model to help increase early initiation of breastfeeding early in hospitals in Lao PDR